Simulating the effect on households' real consumption and poverty of the increase in prices that followed the 2015-16 economic crisis in Mozambique - Félix Mambo; Yonesse Paris; Vincenzo Salvucci; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Poverty declined substantially in Mozambique between 1996/97 and 2014/15. However, the recent economic crisis, characterized by a significant increase in domestic prices, may have dragged several households into poverty. Using consumer price index and 2014/15 household budged survey data, we calculate that the cost of purchasing a basic basket may have risen between 55 per cent and 70 per cent in the period 2014-2016, and we simulate the impact of the rise in prices on households' real consumption and poverty rate. We estimate that the national poverty rate may have risen to 55-60 per cent of the population, from 46,1 per cent estimated in 2014/15. The results of our study provide important elements for a more complete assessment of the microeconomic impact of the 2015-16 crisis and for an analysis of households' vulnerability to sudden prices change. They also inform policymakers about the possible microeconomic impacts of macroeconomic decisions that affect the confidence of international institutions and development partners in the state's economy and institutions.
Keywords: E21; E27; E31; E65; H12; I32; 330; price increase; economic crisis; poverty; simulation; Mozambique